Sustainable Strategies to Current Conditions and Climate Change at U.S. Military Bases and Other Nations in the Arctic Region: A 20-Year Comparative Review - Vinayak Kaushal; Amey Kashyap (Climate, 2024)
Amidst the backdrop of growing great power competition, heightened United States presence via military bases has manifested in the Arctic. However, the then design and implementation have hampered the resilience of these bases in a region warming at nearly four times the rate of the rest of the globe. Two-thirds of the United States’ 79 military bases in the Arctic remain underprepared against permafrost thaw and rising sea levels despite rampant calls for sustainable strategies. Damages emanating from climate-related failures will continue to cost the U.S. billions of dollars and render crucial infrastructure unusable. The objective of this study is to present a comprehensive literature review of the extent of Arctic warming and its significance for U.S. bases, the negative implications of military infrastructure deterioration, and methods to adapt both existing and forthcoming bases to a rapidly warming atmosphere. Eighty published papers that directly or indirectly referenced U.S. military bases or climate-oriented engineering in the aforementioned contexts were identified and analyzed over a 20-year period from 2004 to 2024. The literature review concludes that warming concerns were often not taken into much account by civil engineers during initial base construction, an oversight that now jeopardizes runways, docks, and highways. Other nations that have a sizeable footprint in the Arctic Circle, such as Canada and Russia, have demonstrated progress by utilizing pile-driven substructures, thawing permafrost before construction, and ventilated crawlspaces. Alternative solutions, such as cooling permafrost via thermosiphons or refrigeration systems, employing spatially oriented foundations composed of specific materials, and preventative measures such as floodwalls and revetments, have also shown considerable promise in simulations and practice. A table illustrating a holistic literature summary of sustainable strategies to current conditions and climate change at U.S. Military Bases in the Arctic region is ...